2015
DOI: 10.15403/jgld.2014.1121.243.mew
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation-related Diagnostic and Therapeutic Drug Target Markers in Hepatocellular Carcinoma

Abstract: Glycosylation of cell surface proteins regulate critical cellular functions including migration, growth, proliferation, adhesion and apoptosis. Tumorigenic cells possess gene mutations that alter glycosylation enzyme and substrate quantities resulting in glycosylation changes on the surface of the malignant cell. This may lead to metastasis, uncontrolled proliferation and the inhibition of apoptosis all of which are the hallmarks of cancer. The prevalence of hepatocellular carcinoma (HCC) is increasing worldwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 91 publications
1
21
0
1
Order By: Relevance
“…As is known, migration is crucial for HCC progression [ 32 ]. In this study, we further analyzed the effect of IRAK1 activity on HCC migration.…”
Section: Resultsmentioning
confidence: 99%
“…As is known, migration is crucial for HCC progression [ 32 ]. In this study, we further analyzed the effect of IRAK1 activity on HCC migration.…”
Section: Resultsmentioning
confidence: 99%
“…Although advances have been made in HCC diagnosis and treatment, patient prognosis is poor [15–18]. Sorafenib, the first and only approved targeted therapy for HCC was developed to disrupt the Ras-Raf-MEK1/2-ERK1/2 signaling pathway by specifically targeting Raf-1 kinase and its chemotherapeutic efficacy was correlated with inhibition of MEK and ERK phosphorylation, and other receptor tyrosine kinases, such as VEGFR-2 and 3 [19–21].…”
Section: Discussionmentioning
confidence: 99%
“…An emerging theory in recent years is that the existence of cancer stem cells is the basic cause of the post-operative recurrence of liver tumors (8). The main obstacle is that these cancer stem cells are often in a state of dormancy which impairs the treatment effects of chemotherapeutic drugs (9). Some recent studies have shown that the herpes simplex virus thymidine kinase (HSVtk) gene and the complementary treatment with ganciclovir (GCV) exert marked antitumor effects against HCC by promoting apoptosis and inhibiting angiogenesis (10,11).…”
Section: Introductionmentioning
confidence: 99%